REVIEW: INSTRUMEN KUESIONER PADA PASIEN DIABETES MELITUS - Putra , Erwin Ekadharma; Hermanto, Faizal; Sukandar, Elin Yulinah (Jurnal Buana Farma, 2024)
Diabetes mellitus (DM) is a chronic disease with increasing prevalence worldwide, posing major challenges in patient management and monitoring. Questionnaire instruments are an important tool in DM patient evaluation because they allow systematic and measurable data collection regarding various aspects of the disease, including quality of life, self-management, and perceptions of care. This review article provides a comprehensive overview of various questionnaire instruments used for DM patient evaluation, interpretation of questionnaire results, and grouping based on categories. The review results indicate that the selection of an appropriate instrument must take into account the specific context of the patient population and the evaluation goals. Additionally, we group the evaluation instruments into several categories, including the patient's level of knowledge, compliance with treatment, severity of symptoms, fear of needles, mental condition, and improvement in the patient's quality of life. The conclusion of this article emphasizes the importance of questionnaires in DM management, as well as the need for further research to develop more comprehensive and responsive instruments. Questionnaire instruments, when selected and used appropriately, can improve clinical decision-making and the quality of care provided to DM patients.